"Adherence" and "compliance" in the treatment of psoriasis - literature review - Marcelina Grochowiec; Agata Pakla-Misiur; Joanna Narbutt (Termedia Publishing House, 2016)
Psoriasis, being one of the most common, chronic skin diseases, is not only an important health problem but also a socio-economic issue. The outcome of psoriasis therapy is still unsatisfactory and is influenced by the level of patient compliance and adherence. Outcomes are better with a higher level of compliance, as demonstrated in the studies, and the cost of treatment is lower. Unfortunately, study results indicate a low level of adherence and compliance in patients with psoriasis, and patients and doctors are still not sufficiently aware of the role of these factors in therapy. Based on the studies, there are three main groups of factors which cause non-compliance of patients with treatment recommendations: factors relating to the patient and their health behaviors, factors associated with psoriasis therapy and factors related to the functioning of the health care system.